2015
DOI: 10.1039/c4ra13328e
|View full text |Cite
|
Sign up to set email alerts
|

Nano sized heterogeneous acid catalyst from Ceiba pentandra stalks for production of biodiesel using extracted oil from Ceiba pentandra seeds

Abstract: Heterogeneous acid catalyst of nano size was prepared by the method of sulfonation of C. pentandra stalks and used to convert C. pentandra seed oil to biodiesel. The structure of the catalyst was characterized and physicochemical properties of extracted oil as well as effects of different preparation conditions on biodiesel yield were investigated. A scanning electron microscopy (SEM) photograph showed that the catalyst had a porous structure which enhanced the catalytic ability. From the Brunauer-Emmet-Teller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…However, 4 the trend was reversed when the catalyst loading reached a certain amount, resulting from 5 over catalyst loading would make the esterification of free fatty acid progress faster and more 6 water could be easily formed in a shorter time. However, 4 the trend was reversed when the catalyst loading reached a certain amount, resulting from 5 over catalyst loading would make the esterification of free fatty acid progress faster and more 6 water could be easily formed in a shorter time.…”
Section: Rsc Advances Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…However, 4 the trend was reversed when the catalyst loading reached a certain amount, resulting from 5 over catalyst loading would make the esterification of free fatty acid progress faster and more 6 water could be easily formed in a shorter time. However, 4 the trend was reversed when the catalyst loading reached a certain amount, resulting from 5 over catalyst loading would make the esterification of free fatty acid progress faster and more 6 water could be easily formed in a shorter time.…”
Section: Rsc Advances Accepted Manuscriptmentioning
confidence: 99%
“…19 Fig. Parthiban and 15 Perumalsamy, 4 reported that sulfonic acid group coupled with carbon ring can be formed a 16 stable covalent structure, leading to good stability maintaining at high reaction temperature. It was found to be in the 5 range of 0-15 µm.…”
Section: Rsc Advances Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations